Acute and chronic radiodermatitis: clinical signs, pathophysiology, risk factors and management options. Issue 1 (January 2018) - Robijns, Jolien; Laubach, Hans-Joachim
Abstract : Radiodermatitis (RD) is a cutaneous reaction that occurs as a side-effect of radiotherapy during cancer treatment or sometimes after interventional radiology. There are two forms of RD depending on the time the skin reaction occurs. Acute skin reactions develop a few hours to weeks after the first exposure to radiation, whereas chronic RD can develop months, years or even decades after radiation. Both acute and chronic RD can substantially affect the patients' quality of life and cosmetic outcome. Therefore, a proper prevention and treatment strategy for RD is needed. However, the scientific evidence for effective management options for RD is still lacking. In this paper, we review the most recent literature on the epidemiology, clinical signs, pathophysiology, risk factors and prevention and treatment options for acute and chronic RD caused by radiotherapy and interventional radiology.